Spousal and Survivor Benefits in Option Value Models of Retirement: An Application to Belgium - Alain Jousten; Mathieu Lefèbvre (Institute for the Study of Labor (IZA), 2016)
We study retirement incentives with augmented option value model à la Stock and Wise (1990). We propose methodological extensions to better reflect the respective incentives faced by singles and couples. Our results show that a more comprehensive modelling of couples' incentives leads to very different patterns of retirement incentives – particularly for women. We apply the new indicators to data from the Survey of Health, Ageing and retirement in Europe (SHARE) in Belgium and find two key results. First, contrary to several previous studies, we obtain a positive signed income effects. Second, we find very different retirement incentives for men and women, with little flexibility in the retirement decision for men and substantially more flexibility for women as a function of financial incentives and household composition.
Keywords: H55; J21; J26; 330; retirement; social security; dependent benefits